Teaching, learning and the school environment in the approach of chemistry concepts (Research, Society and Development, 2019)
This work presents an analysis of existing dialogues between teaching, learning and the school environment, in order to identify how they can contribute to the approach of chemical contents. The research, of an exploratory bibliographic nature, counted on the analysis of books, articles, theses and works of events, in order to obtain relevant points about the topics addressed. Chemistry contents are considered by students as difficult to understand because they present abstract concepts and have their own language involving symbols and formulas, and it is necessary to identify ways to change reality and make teaching of chemical concepts more effective. As a result, we highlight the relevance of associating the concepts to the students' daily life, involving the previous knowledge they bring and the use of appropriate teaching methodologies, in order to motivate and give meaning to the contents presented.